How do you find the slant asymptote of #f (x ) = (3x^2 - 2x - 1) / (x + 4 )#?

1 Answer
Apr 16, 2016

Answer:

Slant asymptote is given by #y=3x#

Explanation:

The vertical asymptotes of #(3x^2-2x-1)/(x+4)# are given by zeros of denominator i.e. #x+4=0#.

As the degree of numerator is just one higher than that of denominator, there is no horizontal asymptote, but we do have a slant asymptote given by #y=(3x^2)/x=3x#.

The slant asymptote is given by #y=3x#

graph{(3x^2-2x-1)/(x+4) [-30, 40, -100, 100]}